The Face of Style: 3 in 1 instant cap scarf / Ahmad Kusyaryman Kamaruddin … [et al.] - Kamaruddin, Ahmad Kusyaryman; Azlan, Nurin Balqis; Mohamad Nazri, Nur Hakimah ‘Aliah; Abdul Halim, Nur Syahira Ain (2022)
As partners, we are starting our own company, which we have named The Face of Style. The introduction of a brand-new hijab style and design is our primary commercial activity. Our hijab is strictly "INSTANT SHAWL WITH CAP," we created this product since it is now in style for girls who enjoy wearing a cap and scarf. We designed this new innovation product by attaching the mask strap to a button on the side of the cap. As a result, this design makes it easier for hijab wearers to wear a mask while still being able to style the newest trends which follows the "Syarak" of Islam. The efficient operation of our firm depends on the administrative, marketing, operational, and financial divisions. With one individual working as General Manager and in charge of monitoring all of our company's departments, each of us will be in charge of one of the departments. To make working for us easier, our office is located in our shop lot. It is located in Alam Avenue Seksyen 16, Shah Alam Selangor’s shop. We chose this location since it is currently home to numerous dwellings and has a large population. Therefore, we are attempting to seize this opportunity to draw in and acquire customers. The Face of Style store employs 4 people. Both a bank loan and the partners' own contributions of RM50,000 each are used by Face of Style to fund their business. Our startup business capital and expenses are supported by all of the partner contributions and bank loans. We also intend to use the money to purchase all of the equipment required to run the company. In conclusion, we want The Face of Style to help people achieve beauty and present themselves elegantly.